Soy Isolate Protein Formula: the usage beyond allergy indication - Munasir, Zakiudin; Sekartini, Rini (World Nutrition Journal, 2020)
The usage of soy isolate protein formula for infants was recommended by Indonesian Pediatrics Association (IDAI) through the recommendation of Cow’s Milk Protein Allergy (CMPA) management in 2014. Soy Infant Formula (SIF) has been being used for Infants with Cow’s Milk Protein Allergy (CMPA) as well as for several other related medical indications such as post diarrhea lactose intolerance, galactosemia and primary lactase deficiency1. At early stage of soy formula, it had several deficiencies, infant acceptability, growth, and incomparable with milk-base formula. Current SIF is made from soy protein isolate that contain 2,2 – 2,6 g of protein per 100 calories, it is higher than milk-based formula and both showed same growth and development in Infants2. It contains different fibers, phytate, digestibility, protease inhibitor and proteins. SIF is easily digestible and contain high amino acid content fortified with L-methionine, L-carnitine and taurine. High content of phytate is overcome with zinc and iron fortification as well as increased levels of calcium and phosphor3. American Academy of Pediatrics recommends isolated soy protein-based formulas as a safe and effective alternative for providing appropriate nutrition for normal growth and development for term infants whose nutritional needs are not being met from maternal breast milk or cow’s milk-based formulas3,4.